ANALISIS PENDAPATAN PETERNAKAN ITIK BALI DENGAN PEMBERIAN JUS DAUN INDIGOFERA (Indigofera zollingeriana) - Putra V. E.; B.R.T. Putri; G. Suarta (Jurnal Peternakan Tropika, 2023)
This study aims to determine the income of Bali Duck farming by giving indigofera leaf juice (Indigofera zollingeriana). This research was conducted for two months at Sesetan Farm, Faculty of Animal Science, Udayana University, Denpasar. The design used was a completely randomized design (CRD) consisting of 4 treatments and 5 replications with 120 bali ducks used. The treatments were drinking water without indigofera leaf juice which was used as a control (A), drinking water given indigofera leaf juice as much as 2% (B), drinking water given indigofera leaf juice as much as 4% (C) drinking water given juice indigofera leaves as much as 6% (D). The observed variables include income analysis based on costs, revenues, income, R/C ratio and BEP. The results of the income analysis showed that ducks with 4% indigofera leaf juice gave the best results with an income of Rp 406,561,-/period with an R/C ratio of 1.225. BEP of production units is 36,059 kg live ducks, BEP selling price of ducks per kg is Rp 40,799,-/kg live weight, and BEP for revenue is Rp 1,802,950/period. Based on the results of the study, it can be concluded that Bali duck farming by giving indigofera leaf juice (Indigofera zollingeriana) can increase the income of farmers. Keywords: Income analysis, duck and indigofera leaf juice